Analisis Kebutuhan Pergerakan untuk Pengembangan Jaringan Jalan di Kota Lubuklinggau - Meliana, Eta; Buchari, Erika; Agustien, Melawaty (Jurnal Rekayasa Sipil dan Lingkungan, 2023)
The suitability of road class and service is an important thing that impacts the road's capacity. Currently, in Lubuklinggau City, district/city roads have the same level of service as national roads, with high traffic flows resulting from changes in land use. Road class change plants were analyzed using a four-stage transportation modeling method and processed with a post-mortem program and analysis of service levels and suitability of road classes with MKJI 1997 Level of Service (LOS) and Volume Capacity Ratio (VCR). The locations examined were Yossudarso Street and Letkol Sukirno Lapter Street, south ring of Lubuklinggau City. The traffic volume of Yossudarso Street obtained from the application visum was 2,053 pcu/hour. The traffic account survey results were 2,019 pcu/hour, and Letkol Sukirno Lapter Street obtained from the application visum was 1,718 pcu/hour, and the traffic account survey results were 1,705 pcu/hour. VCR value on Yossudarso Street is 0.72, Letkol Sukirno Street 0.60, Yossudarso Street is 0.72, and Letkol Sukirno Street is 0,60. The level of service for both roads is C. ABSTRAK Kesesuaian kelas jalan dengan pelayanan jalan merupakan hal penting yang berdampak pada kemampuan daya tampung jalan tersebut. Saat ini di Kota Lubuklinggau jalan kabupaten/kota tingkat pelayanannya sudah setara jalan Nasional tingginya arus lalu lintas yang terjadi akibat dari perubahan tata guna lahan. Analisis rencana perubahan kelas jalan dilakukan dengan menggunakan metode empat tahap permodelan transportasi dan diolah dengan program visum dan analisa tingkat pelayanan dan kesesuaian kelas jalan dengan MKJI 1997 Level of Service (LOS) dan Volume Capacity Ratio (VCR). Lokasi yang di teliti yaitu Jalan Yossudarso dan Jalan Letkol Sukirno Lapter Lingkar Selatan Kota Lubuklinggau. Volume lalu lintas Jalan Yossudarso diperoleh dari program visum 2.053 smp/jam dan hasil survei traffic count 2.019 smp/jam dan Jalan Letkol Sukirno Lapter Lingkar Selatan diperoleh dari aplikasi visum sebesar 1.718 smp/jam dan hasil survei traffic count 1.705 smp/jam. Nilai VCR di jalan Yossudarso 0,72, jalan Sukirno Lapter 0,60, jalan Yossudarso 0,72 dan jalan Sukirno Lapter 0,60. Tingkat pelayanan kedua jalan tersebut adalah C.